2003
DOI: 10.1046/j.1365-313x.2003.01909.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Arabidopsis SHY2/IAA3 protein turnover

Abstract: SummaryAuxin/indole acetic acid (Aux/IAA) proteins regulate transcriptional responses to the plant hormone auxin. Gain-of-function mutations in the Arabidopsis SHORT HYPOCOTYL 2 (SHY2/IAA3 ) gene encoding an Aux/ IAA protein increase steady-state levels of SHY2/IAA3 protein and decrease auxin responses, indicating that SHY2/IAA3 negatively regulates auxin signaling. These shy2 mutations also cause ectopic light responses, suggesting that SHY2/IAA3 may promote light signaling. Auxin regulates turnover of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 59 publications
3
85
0
Order By: Relevance
“…3b); (2) the decrease and elimination of IAA-induced membrane potential hyperpolarisation by NQ and NQ-2-OH; (3) the induction of the alkalinisation of the medium and membrane depolarisation by the highest naphthoquinone concentrations and (4) the increase in H 2 O 2 production, which may indirectly inhibit PM H + -ATPase. Tian et al (2003) found that juglone (5-hydroxy-1,4-naphthoquinone) inhibit the interaction between the IAA/AUX transcriptional repressor and SCF-TIR1 and lead to the decrease of auxin genes expression. Taking above into account it can be suggested that 1,4naphthoquinone and 2-hydroxy-1,4-naphthoquinone can similarly affect auxin nuclear signaling system.…”
Section: Discussionmentioning
confidence: 99%
“…3b); (2) the decrease and elimination of IAA-induced membrane potential hyperpolarisation by NQ and NQ-2-OH; (3) the induction of the alkalinisation of the medium and membrane depolarisation by the highest naphthoquinone concentrations and (4) the increase in H 2 O 2 production, which may indirectly inhibit PM H + -ATPase. Tian et al (2003) found that juglone (5-hydroxy-1,4-naphthoquinone) inhibit the interaction between the IAA/AUX transcriptional repressor and SCF-TIR1 and lead to the decrease of auxin genes expression. Taking above into account it can be suggested that 1,4naphthoquinone and 2-hydroxy-1,4-naphthoquinone can similarly affect auxin nuclear signaling system.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Arabidopsis domain II mutant proteins iaa3/shy2, iaa7/axr2-1 and iaa17/axr3-1, which carry mutations in the highly conserved proline residues (see Supplementary Fig. 2), are incapable of binding the TIR1 receptor 4,5,7,13,15 . These observations, together with the results presented in Figs 1 and 2, raise the possibility that LRT2-catalysed cis/trans isomerization of OsAux/IAAs is critical for the formation of a functional OsTIR1-OsIAA co-receptor.…”
Section: Lrt2 Catalyses Cis/trans Isomerization Of Osiaa11 Peptidementioning
confidence: 99%
“…Genetic studies reveal that various gain-of-function mutations in domain II, largely located in the highly conserved central Gly-Trp-Pro-Pro-Val (GWPPV) motif, render Aux/ IAAs resistant to the auxin-induced proteasomal degradation, resulting in a dominant auxin insensitive phenotype [7][8][9][10][12][13][14] . Notably, the auxin-dependent interaction between TIR1 and Aux/IAAs is reduced or abolished by mutations in the GWPPV motif, illustrating the critical role of the domain II-mediated degradation of Aux/IAAs in auxin signalling 4,5,7,13,15 . Consistent with these observations, the analysis of the crystal structure of the Arabidopsis TIR1-auxin-IAA7 peptide complex reveals that the GWPPV motif of domain II is crucial for the formation of the coreceptor complex 6 .…”
mentioning
confidence: 99%
“…The degradation of the AUX/IAA proteins is mediated by the proteasomal pathway, which typically involves ubiquitination by E3-ubiquitin ligases (19). We investigated whether the changes in auxin responsiveness during the activity-dormancy transition involve alterations in the proteasomal degradation of AUX/IAA proteins as shown for Arabidopsis AUX/IAA proteins (20)(21)(22)(23)(24). For this, we analyzed the ubiquitination of a GST fusion of PttIAA3, a poplar AUX/IAA gene expressed in the cambial meristem in hybrid aspen (25).…”
Section: Establishment Of Endodormancy Is Correlated With the Loss Ofmentioning
confidence: 99%